Central Nervous System Double Relapse of Acute Promyelocytic Leukemia and Acute Myelomonocytic Leukemia. (18th December 2019) - Stanko, Laura M.; Reddy, Vishnu; Mikhail, Fady M.; Papadantonakis, Nikolaos
Abstract : Relapse of acute promyelocytic leukemia (APL) and non-M3-acute myeloid leukemia in the central nervous system (CNS) are rare events. Here, we describe a case of simultaneous relapses of APL and acute myelomonocytic leukemia on the CNS of a patient after allogeneic bone marrow transplant. This extremely unusual case highlights the difficulties that CNS leukemia relapses pose in the post-transplant setting.